Identifying novel drugs for the treatment of rhabdomyosarcoma - Bleloch,Jenna (Department of Human Biology, 2022)
Rhabdomyosarcoma (RMS) forms in skeletal muscle and is the most common soft tissue sarcoma in children and adolescents. Current treatment is associated with debilitating side effects and treatment outcomes for patients with metastatic disease are dismal. Other than a need for alternative and more effective therapies there is also a growing appreciation for the need to understand the molecular underpinnings of RMS with the aim of identifying, in part, novel targets to develop highly specific and effective treatments with negligible adverse effects. The aim of this study was to identify novel drugs for the treatment of the two major RMS subtypes viz alveolar (ARMS) and embryonal (ERMS) RMS and to do so it adopted a two-pronged approach. Firstly, a novel binuclear palladacycle, AJ-5, was investigated for its anti-cancer activity and its mechanism(s) of action in RMS cells. The second approach involved a target-based drug repurposing strategy where a library of FDA-approved drugs was screened to identify leads that were able to negatively regulate the oncogenic TBX2 and TBX3 transcription factors that are known drivers of RMS. The binuclear palladacycle, AJ-5, was recently shown to exert potent cytotoxicity in melanoma and breast cancer and to present with negligible adverse effects in mice. To investigate the anti-cancer activity of AJ-5 in RMS cells, MTT assays were firstly performed in ERMS and ARMS as well as 'normal' cells. IC50 values determined from these experiments showed values of ≤ 0.2μM for the RMS cells and a favourable selectivity index of > 2. Clonogenic and migration assays showed that AJ-5 inhibited the ability of RMS cells to survive and migrate respectively. Western blotting revealed that AJ-5 induced levels of key DNA damage response proteins (γH2AX, p-ATM and p-Chk2) and the p38/MAPK stress pathway. This correlated with an upregulation of p21 and a G1 cell cycle arrest. Annexin V-FITC/propidium iodide staining revealed that AJ-5 induced apoptotic and necrotic cell death. Apoptosis was confirmed by the detection of cleaved PARP and increased levels and activity of cleaved caspases-3, -7, -8 and -9. Increased levels of necroptotic markers p-RIP3 and p-MLKL and inhibition of necroptosis with necrostatin-1 with a corresponding significant increase in cell viability suggests that AJ-5 is also capable of triggering a form of programmed necrosis. Furthermore, AJ-5 reduced autophagic flux as shown by reduced LC3II accumulation in the presence of bafilomycin A1, and a significant reduction in autophagosome flux J. Pharmacokinetic studies in mice show that AJ-5 has a promising half-life and that its volume of distribution is high, its clearance low and its intraperitoneal absorption is good. With the intention of improving the drug-like properties of AJ-5, specifically its water solubility, a derivative of AJ-5, BTC2, was synthesised and identified to display comparable anti-cancer activity against ERMS and ARMS cells. Together these findings suggest that AJ-5 and BTC2 may be effective chemotherapeutics with a desirable and novel mechanism of action for treating drug resistant and advanced RMS. The highly homologous T-box transcription factors TBX2 and TBX3 have both been implicated as key drivers of RMS and they have been identified as novel therapeutic targets for the treatment of this sarcoma subtype. Indeed, TBX2 or TBX3 overexpression in normal myoblasts inhibits muscle differentiation and overexpression and knock-down cell culture and mouse models show that RMS cells are addicted to them for their cancer phenotype. However, targeting transcription factors is notoriously challenging because unlike enzymes they do not have catalytic activity and deep binding pockets to which small molecule inhibitors can be designed which is further exacerbated by the length of time and costs associated with de novo drug development. Therefore, this study adopted a novel strategy to circumvent these challenges by combining a drug repurposing with a targeted approach to TBX2/3. Briefly, a high throughput cell-based immunofluorescence screen was designed and conducted to identify FDA-approved drugs that could negatively regulate TBX2 and/or TBX3 protein levels or nuclear localisation. Cells were engineered to express induced exogenous FLAG-tagged TBX2 and TBX3 using a Tet-On system and they were screened with the Pharmakon 1600 drug library at a concentration of 10μM. 'Hits' were identified by z-scores and amongst these, niclosamide, piroctone olamine and pyrvinium pamoate were validated to be potent inhibitors of TBX2/3 and were shown to display anti-cancer activity in RMS. These drugs have the potential to be repurposed for the treatment of RMS and other TBX2/3 driven cancers either as single agents or in combination with currently used chemotherapeutics.